The impact of CGIAR centre research on use of planted forages by tropical smallholders - Duncan, Alan J.; Peters, Michael; Schultze-Kraft, Rainer; Thornton, Philip K.; Teufel, Nils; Hanson, Jean; McIntire, John M. (CAB International, 2020)
This chapter provides information on the common problems faced by livestock farmers in Africa and Asia, such as insufficient availability of high-quality feed, declines in grazing resources in response to the expansion of cultivated land and poor control over grazing rights, among others. The importance of the cultivation of green forages specifically for feeding livestock as a potential means of addressing the feed gap is discussed. The potential and actual impact of planted forages are presented and success cases emerging from CGIAR research are reviewed.